Estrogen receptor coregulators and pioneer factors: the orchestrators of mammary gland cell fate and development - Manavathi, Bramanandam; Samanthapudi, Venkata S. K.; Gajulapalli, Vijay Narasimha Reddy (Frontiers in Cell and Developmental Biology, 2014)
The 17-beta estradiol (E2), a steroid hormone, which play critical role in various cellular processes such as cell proliferation, differentiation, migration and apoptosis, is essential for reproduction and mammary gland development. E2 actions are mediated by two classical nuclear hormone receptors, estrogen receptor alpha and beta (ERs). The activity of ERs depends on the coordinate activity of ligand binding, posttranslational modification, and importantly their interaction with their partner proteins called ‘coregulators’. Because majority of breast cancers are ERalpha positive and coregulators are proved to be crucial for ER transcriptional activity, an increased interest in the field has led to the identification of a large number of coregulators. In the last decade, gene knockout studies using mouse models provided impetus to our further understanding of the role of these coregulators in mammary gland development. Several coregulators appear to be critical for terminal end bud formation, ductal branching and alveologenesis during mammary gland development. The emerging studies support that, in addition to these coregulators, the other ER partner proteins ‘pioneering factors’ also seems to contribute significantly to E2 signaling and mammary cell fate. This review discusses emerging themes in coregulator- and pioneering factor-mediated action on ER functions, particularly their role in mammary gland cell fate and development.